Impedance Spectroscopy, Electrical Relaxation and Ac Conductivity Studies of an Organic-Inorganic Hybrid Compound: C12H14N2CuCl4 - Wamani, W.; Elwej, R.; Mhiri, T.; Belhouchet, Mohamed (JOURNAL OF ADVANCES IN CHEMISTRY, 2009)
The AC conductivity of the compound, C12H14N2CuCl4, in the temperature and frequency range from 373 to 423 K and 209 Hz â€“ 5 MHz, respectively, is reported. The differential scanning calorimetry and thermogravimetric analysis indicate the presence of a phase transition at 400 K. The Zâ€™ and Zâ€™â€™ vs. frequency plots are found to be well fit by using the equivalent circuit model. The circuits consist of a parallel combination of bulk resistance Rp and constant phase element. Besides, the analysis of the experimental data based on the jump relaxation model shows that the translation motion of the charge carrier and reorientation hopping between the equivalent sites of the metal chloride anion and the cation groups are responsible for the observed AC conductivity in the temperature regions I (373â€“400 K) and II (400â€“423 K). The frequency dependence of the conductivity which follows the Arrhenius equation is interpreted in terms of Jonscher’s law: Ïƒ (Ï‰) = Ïƒdc +A Ï‰ S.Â